Progress at JET in integrating ITER-relevant core and edge plasmas within the constraints of an ITER-like wall. (10th February 2015) - Giroud, C; Jachmich, S; Jacquet, P; Järvinen, A; Lerche, E; Rimini, F; Aho-Mantila, L; Aiba, N; Balboa, I; Belo, P; Angioni, C; Beurskens, M; et al.
Abstract: This paper reports the progress made at JET-ILW on integrating the requirements of the reference ITER baseline scenario with normalized confinement factor of 1, at a normalized pressure of 1.8 together with partially detached divertor whilst maintaining these conditions over many energy confinement times. The 2.5 MA high triangularity ELMy H-modes are studied with two different divertor configurations with D-gas injection and nitrogen seeding. The power load reduction with N seeding is reported. The relationship between an increase in energy confinement and pedestal pressure with triangularity is investigated. The operational space of both plasma configurations is studied together with the ELM energy losses and stability of the pedestal of unseeded and seeded plasmas. The achievement of stationary plasma conditions over many energy confinement times is also reported.